2006
DOI: 10.1200/jco.2006.24.18_suppl.6508
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib in patients with chronic phase chronic myeloid leukemia (CP-CML) who are resistant or intolerant to imatinib: Results of the CA180013 ’START-C’ Study

Abstract: 6508 Background: Dasatinib (BMS-354825) is a novel, oral, multi-targeted kinase inhibitor of BCR-ABL and SRC kinases with proven preclinical and clinical activity against imatinib resistant BCR-ABL mutations. Methods: CA180013 is an open-label Phase II study of dasatinib in imatinib-resistant (IM-R) or -intolerant (IM-I) patients (pts) with CP-CML. Between February-August 2005, 424 pts were recruited from 75 centers worldwide. Dasatinib was given at 70 mg twice daily (BID) with dose escalation to 90 mg BID in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Phase II studies for dasatinib [32][33][34][35] in all phases of CML and Ph + ALL have been reported and supported rapid ap- proval of the compound (named Sprycel) on 6/29/06 for both indications; the recommended dose is 70 mg BID. In the "Start-C" trial of dasatinib in CP CML, 32 60% of patients required dose reductions over time for toxicity and the median dose was closer to 100 mg per day; ongoing trials continue to explore dosing options for dasatinib, including varying total dose and QD versus BID dosing.…”
Section: New Therapy To Address Imatinib-resistant Diseasementioning
confidence: 93%
“…Phase II studies for dasatinib [32][33][34][35] in all phases of CML and Ph + ALL have been reported and supported rapid ap- proval of the compound (named Sprycel) on 6/29/06 for both indications; the recommended dose is 70 mg BID. In the "Start-C" trial of dasatinib in CP CML, 32 60% of patients required dose reductions over time for toxicity and the median dose was closer to 100 mg per day; ongoing trials continue to explore dosing options for dasatinib, including varying total dose and QD versus BID dosing.…”
Section: New Therapy To Address Imatinib-resistant Diseasementioning
confidence: 93%
“…Complete hematological response was obtained in 90% of patients. 63 The START-A enrolled 192 patients with accelerated phase CML resistant or intolerant to imatinib; 174 patients received treatment. Major hematological response, the primary objective, was obtained in 102 of 174 patients.…”
Section: Dasatinibmentioning
confidence: 99%